Factors affecting consumers’ intention towards mobile banking in Malaysia - Chooi, Jia Lee; Loh, Su Cheng; Tan, Siao Wei; Tang, Xian Zhen; Yu, Jia Ling (2021)
The objective of this study is to examine the factors affecting consumers’ intention towards mobile banking in Malaysia. This study focused on the investigation of the relationship between the four independent variables such as perceived ease of use, perceived usefulness, social influence, and security concern and the consumers’ intention towards mobile banking in Malaysia. A primarily source of data are employed to achieve the objective of this study. The primary data are collected through distributing online questionnaire with 5-point Likert scale to the respondents by using Google Form. The target population of this study is the bank consumers who are non-users and existing users of mobile banking in Malaysia. A total of 389 sets of questionnaires and Smart-PLS Version 3.3.3 are used to conduct the data analysis. The Partial Least Squares (PLS) of Structural Equation Modelling (SEM) method are adopted in this study. The findings of this study showed that the perceived ease of use, perceived usefulness, and social influence have significance relationship with the consumers’ intention towards mobile banking in Malaysia. However, security concern do not have significance relationship with the consumers’ intention towards mobile banking in Malaysia. This study provided several limitations and recommendations to the future researchers for improvements and this study is advantageous for businesses, especially financial institutions and fintech companies.